PENGARUH MODEL ROUNDTABLE TERHADAP KEMAMPUAN KERJASAMA DAN BERCERITA SEJARAH SISWA KELAS XII AKUNTANSI SMKN 1 BLEGA - Khoironi, Iqbal; Tobing, Victor Maruli Tua L.; Isman, Soubar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The objectives of this research include: 1) To determine the influence of the roundtable learning model on the collaboration abilities of class Knowing the influence of the roundtable learning model on the ability to collaborate and tell history of class XII Accounting students at SMKN 1 Blega. Researchers chose one approach in carrying out this research, namely a quantitative approach. Quantitative research has systematic research stages, making it easier for researchers to carry out each research stage. The researcher used Nonequivalent Control Group Design as an experimental research design and is a derivative of quasi experimental design. The sample in this study was 22 students from class XII TBSM 2 as the control group and 22 students from class XII RPL as the experimental class. Researchers developed an instrument in the form of a questionnaire to collect data on students' cooperation abilities during history lessons. The second research instrument developed was a practical storytelling test along with an assessment sheet for students' historical storytelling abilities. The research conclusions include: 1) There is an influence of the roundtable learning model on the cooperative abilities of class on the ability to collaborate and tell the history of class XII Accounting students at SMKN 1 Blega.